2022
DOI: 10.3390/en15051892
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Grid-Connected PV-Battery System of Mongolian Ger

Abstract: One of the main sources of energy utilized in the Mongolian Gers is coal and wood mainly for the purpose of heating and other domestic use. This heavily increases the air pollution levels. A viable solution for handling the air pollution is switching to renewable energy sources (RES). Grid-connected photovoltaic (PV) systems with battery back-up provide a reliable solution to the problem addressing the energy demand and pollution control. This paper proposes a grid-connected PV–second-life battery system and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This scheme might be able to lift a huge financial burden off the customers. In our previous study [4], an economic analysis in a private ger with a PV-battery system demonstrated that the deployment of PV systems has the potential to be profitable.…”
Section: Introductionmentioning
confidence: 99%
“…This scheme might be able to lift a huge financial burden off the customers. In our previous study [4], an economic analysis in a private ger with a PV-battery system demonstrated that the deployment of PV systems has the potential to be profitable.…”
Section: Introductionmentioning
confidence: 99%